Helyi önkormányzati autonómia: mi változik, mi marad? (Autonomy of local governments: what will change, what will remain?) - Katalin Adél Rámhápné Radics (KözigazgatásTudomány)
In Hungary, the autonomy of local governments has always been an important issue in balancing local democracy with central state control. Looking back over the past 35 years, the issue first gained particular importance during the 1989-90 regime change. The reform of local government in 2012 brought the issue of autonomy back to the forefront, with a change of model that affected both the substance and form of the autonomy of local governments. The present study focuses on the issue of the autonomy of local governments. After a brief overview of the meaning of autonomy and the basic elements of local government autonomy, I will examine the changes in the extent of local government autonomy by tracing specific legislative changes. In conclusion of the research findings, it can be said that in the last few years in Hungary, the autonomy of local governments has faced serious challenges due to the changing political environment.